Efficacy and Safety of Low-Dose Chlorambucil in Nephrotic Patients with Idiopathic Membranous Nephropathy - Idasiak-Piechocka, Ilona; Oko, Andrzej; Łochyńska-Bielecka, Katarzyna; Skrobańska, Beata (Kidney & blood pressure research, 2009)
Aim: This observational study aimed to evaluate the results of treatment with low-dose chlorambucil in combination with corticosteroids in patients with idiopathic membranous nephropathy (iMGN) and nephrotic syndrome. Methods: Thirty-two patients with nephrotic syndrome and biopsy-proven iMGN were included in the study. At presentation, 9 patients were found to be in stage 1, 13 patients in stage 2 and 10 patients in stage 3 chronic kidney disease. In all patients, i.v. methylprednisolone pulses (500 mg/day for 3 days) were administered, followed by oral prednisone at an initial dose of 1 mg/kg per day, tapered gradually after 8 weeks to the maintenance dose of 5 mg/day after 6 months, and chlorambucil 2 mg twice daily for 6 months. Results: Complete remission of nephrotic syndrome was obtained in 14 patients (47.3%) and partial remission in 16 patients (50%). Two patients relapsed after 1 year of treatment. We did not record any severe side effects in treated patients, except glucose intolerance in 4 subjects on high corticosteroid doses. Conclusion: Immunosuppressive treatment with corticosteroids and low-dose chlorambucil seems to be effective and well tolerated in nephrotic patients with iMGN.